2013
DOI: 10.1371/journal.pone.0059958
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Characterisation of Tumor Necrosis Factor Alpha and Interleukin-10 Responses to Chlamydia pecorum Infection in the Koala (Phascolarctos cinereus)

Abstract: Debilitating infectious diseases caused by Chlamydia are major contributors to the decline of Australia's iconic native marsupial species, the koala (Phascolarctos cinereus). An understanding of koala chlamydial disease pathogenesis and the development of effective strategies to control infections continue to be hindered by an almost complete lack of species-specific immunological reagents. The cell-mediated immune response has been shown to play an influential role in the response to chlamydial infection in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
4
27
2
Order By: Relevance
“…Although the short incubation times employed in the current study would be an advantage when stimulating samples from this wildlife species in the field, it may be that the study of IL-6 and ILwill require more extended incubation and, possibly, specific mitogens. Up-regulation of IL-10 in the present study was less than that reported by Mathew et al (Mathew et al 2013a) following antigen stimulation (by UV inactivated C. pecorum particles). In addition, although some individuals showed evidence of IL-6 up-regulation, there was no significant increase in IL-6 expression among treatment groups.…”
contrasting
confidence: 91%
See 3 more Smart Citations
“…Although the short incubation times employed in the current study would be an advantage when stimulating samples from this wildlife species in the field, it may be that the study of IL-6 and ILwill require more extended incubation and, possibly, specific mitogens. Up-regulation of IL-10 in the present study was less than that reported by Mathew et al (Mathew et al 2013a) following antigen stimulation (by UV inactivated C. pecorum particles). In addition, although some individuals showed evidence of IL-6 up-regulation, there was no significant increase in IL-6 expression among treatment groups.…”
contrasting
confidence: 91%
“…All sequences possessed key conserved residues, confirming their identity (Fig 1 and 2, Supplementary Material A). Sequences for IL-10, and IFNγ were consistent with those of Mathew et al (Mathew et al 2013a;Mathew et al 2013b). Sequences have been lodged in GenBank under the accession numbers: PhciCD4, KF731654;…”
Section: Partial Sequence Of Koala Immune Genessupporting
confidence: 79%
See 2 more Smart Citations
“…Due to constant pathogen-driven selection, immune molecules are among the least conserved between species. Our ability to examine koala immune profiles has, therefore, been limited to detection of antibodies, lymphocyte proliferation assays, immunophenotyping by flow cytometry with a limited number of cross-reactive antibodies to conserved (mostly intra-cytoplasmic) domains (T cell, anti-human CD3; B cell, anti-human CD79b; MHCII, anti-human HLA-DP, DQ, DR; IFNg) (Higgins et al, 2004;Lau et al, 2012) and, very recently, qPCR for IL10, IFNg and TNFa (Mathew et al, 2013a;2013b). Our recent immunophenotypic studies on captive, KoRV-positive koalas (Lau et al, 2012) revealed some interesting features: elevated numbers of B cells relative to other species (1.0-4.9×10 6 cells/ml vs 0.17-0.56×10 6 cells/ml, respectively), and absence of MHCII expression on stimulated and nonstimulated T cells.…”
Section: Is Korv Immunomodulatory In Koalas?mentioning
confidence: 99%